Combination Therapy for Cryptosporidiosis in Immunocompromised Patients: A Systematic Review - Utami, Wiwien Sugih; Rozaq, M.S. Irham; Indreswari, Laksmi; Abrori, Cholis; Hermansyah, Bagus (Folia Medica Indonesiana, 2024)
Cryptosporidium sp. is a gastroenteritis-causing pathogen that may increase mortality and morbidity in immunocompromised patients. Diarrhea is a common problem among acquired immunodeficiency syndrome (AIDS) patients, with 30–60% of patients in developed countries and 90% in developing countries affected. The prevalence of cryptosporidiosis is 3–5% of the global population, with 14.42% of those affected being immunocompromised. There is currently no vaccine available to prevent cryptosporidiosis, while nitazoxanide monotherapy is ineffective in eradicating the organism in immunocompromised hosts and malnourished children. This study aimed to determine the most effective combination therapy for cryptosporidiosis in immunocompromised patients. This study used a systematic review design and implemented eligibility criteria for the literature search across PubMed, ScienceDirect, Epistemonikos, Google Scholar, Nature, Springer, and John Wiley databases. The search utilized specific keywords and Boolean operators, i.e., “Cryptosporidium,” OR “cryptosporidiosis,” AND “combination therapy,” OR “combination treatment,” AND “immunocompromised.” Two cohort studies and two case reports were selected, three of which used a nitazoxanide and azithromycin combination as the intervention, whereas only one cohort study used a nitazoxanide and fluoroquinolone combination. The studies comprised 54 samples from post-kidney transplantation patients and one sample from an acute lymphoblastic leukemia (ALL) patient. The nitazoxanide and fluoroquinolone combination showed superior outcomes than the nitazoxanide and azithromycin combination. The stool clearance was significantly lower with nitazoxanide monotherapy than the nitazoxanide and fluoroquinolone combination (OR=0.65, 95% CI=0.34–0.92, p=0.01). However, it was non-significantly lower with the nitazoxanide and azithromycin combination compared to monotherapy (OR=0.27, 95% CI=0.01–5.77, p=0.24). Nitazoxanide monotherapy exerted a significantly lower effect than the nitazoxanide and fluoroquinolone combination in stopping diarrhea symptoms (OR=0.45, 95% CI=0.21–0.81, p=0.004). In conclusion, a combination therapy using nitazoxanide and fluoroquinolone for cryptosporidiosis in immunocompromised patients offers more favorable outcomes compared to monotherapy, particularly in stopping diarrhea and enhancing stool clearance.